New Aspects on Listeria monocytogenes ST5-ECVI Predominance in a Heavily Contaminated Cheese Processing Environment - Muhterem-Uyar, Meryem; Ciolacu, Luminita; Wagner, Karl-Heinz; Wagner, Martin; Schmitz-Esser, Stephan; Stessl, Beatrix (Frontiers in Microbiology, 2018)
The eradication of L. monocytogenes from food chains is still a great challenge for the food industry and control authorities since some clonal complexes are either better adapted to food processing environments (FPEs) or are globally widespread. In this work, we focus on the in-house evolution of L. monocytogenes genotypes collected from a heavily contaminated food processing environment whose contamination pattern underwent a massive and yet unexplained change. At the beginning of the sampling in 2010, a high variety of most likely transient L. monocytogenes genotypes was detected belonging to sequence type (ST) 1, ST7, ST21, ST37. After several efforts to intensify the hygiene measures, the variability was reduced to L. monocytogenes ST5 that was dominant in the following years 2011 and 2012. We aimed to elucidate possible genetic mechanisms responsible for the high abundance and persistence of ST5 strains in this FPE. Therefore, we compared the genomes of six L. monocytogenes ST5 strains to the less frequently occurring transient L. monocytogenes ST37 and ST204 from the same FPE as well as the highly abundant ST1 and ST21 isolated in 2010. Whole genome analysis indicated a high degree of conservation among ST5 strains [average nucleotide identity (ANI) 99.93-99.99%; tetranucleotide correlation 0.99998-0.99999]. Slight differences in pulsed field gel electrophoresis (PFGE) patterns of two ST5 isolates could be explained by genetic changes in the tRNA-Arg-TCT prophages. ST5 and ST204 strains harbored virtually identical 91 kbp plasmids related to plasmid group 2 (pLM80 and pLMUCDL175). Interestingly, highly abundant genotypes present in the FPE in 2010 did not harbor any plasmids. The ST5 plasmids harbored an efflux pump system (bcrABC cassette) and heavy metal resistance genes possibly providing a higher tolerance to disinfectants. The pLM80 prototype plasmids most likely provide important genetic determinants for a better survival of L. monocytogenes in the FPE. We reveal short-term evolution of L. monocytogenes strains within the same FPE over a three year period and our results suggest that plasmids are important for the persistence of ST5 strains in this FPE.